THE MYSTERIANISM OF OWEN FLANAGAN'S NORMATIVE MIND SCIENCE. - Leidenhag, Mikael (Zygon: Journal of Religion & Science, 2018)
Abstract: This article critically analyzes Owen Flanagan's physicalism and attempt at deriving ethical normativity from current neuroscience. It is argued that neurophysicalism, despite Flanagan's harsh critique of “the new mysterians,” entails a form of mysterianism and that it fails to appropriately ground human mentality within physicalism. Flanagan seeks to bring spirituality and a physicalist ontology together by showing how it is possible to derive an account of the good life from science. This attempt is critiqued and it is shown that Flanagan fails to establish the consistency between ethical normativity and physicalism. Hence, another form of mysterianism seems to emerge within this normative mind science.